Advocate : On History's Front Lines from Watergate to the Keating Five, Clinton Impeachment, and Benghazi - Hamilton, James, 1938- (Book collections on Project MUSE., 2022)
"James Hamilton has been a fly on the wall of American history through his involvement in the investigations concerning Watergate, the Kennedy assassination, "Debategate," the Keating Five, the Clinton impeachment, Vince Foster's suicide, the Valerie Plame affair, Benghazi, and the Major League Baseball steroids scandal. Arguing against Brett Kavanaugh (in Kavanaugh's only Supreme Court argument), Hamilton won the Supreme Court case establishing that the attorney-client privilege survives death. Written in clear, incisive prose, Watergate and Beyond discusses the travails of prominent politicians and other well-known individuals, focusing particularly on high-profile Congressional and other investigations, and discusses Hamilton's extensive vetting of Vice Presidential, Cabinet and Supreme Court candidates-including Joe Biden, John Edwards, and Ruth Ginsberg. The book concludes with practical advice for young lawyers entering the profession. Much more than a memoir from a seasoned lawyer, Watergate and Beyond is a richly detailed history of some of the most sensational and controversial events in Washington politics over the past half-century. Anyone interested in the uniquely American intermingling of law and politics will find this an engaging read"--